Incidencia de la didáctica constructiva aplicada en el área de informática en el rendimiento académico de los estudiantes del ciclo básico, en la sección vespertina del Colegio Juan Montalvo de la ciudad de Machala, durante el periodo lectivo 2012-2013. - León Cedeño, Noyra Maribel (2013)
For our society and its optimal performance, it is vitally important to pay attention to a serious and responsible to the educational field, as it is in this environment where we sow the foundation for our long-awaited society. By virtue has done this research to have a point of much more accurate and objective about how it is carrying out the process of teaching and learning in the classroom view, and specifically in the Basic Cycle School Juan Montalvo national Science city of Machala.